Communicative Competence for Individuals who require Augmentative and Alternative Communication: A New Definition for a New Era of Communication?. (March 2014) - Light, Janice; McNaughton, David
Abstract In 1989, Light defined communicative competence for individuals with complex communication needs who require augmentative and alternative communication (AAC) as a dynamic interpersonal construct based on functionality of communication; adequacy of communication; and sufficiency of knowledge, judgment, and skills. Specifically, Light argued that, in order to demonstrate communicative competence, individuals who required AAC had to develop and integrate knowledge, judgment, and skills in four interrelated domains: linguistic, operational, social, and strategic. In 2003, Light expanded this definition and argued that the attainment of communicative competence is influenced by not just linguistic, operational, social, and strategic competencies but also a variety of psychosocial factors (e.g., motivation, attitude, confidence, resilience) as well as barriers and supports in the environment. In the 25 years since this definition of communicative competence for individuals who use AAC was originally proposed, there have been significant changes in the AAC field. In this paper, we review the preliminary definition of communicative competence, consider the changes in the field, and then revisit the proposed definition to determine if it is still relevant and valid for this new era of communication.